Exploring the efficacy of premarital counselling in church settings: A qualitative study - Bakadzi Moeti; Tshenolo J. Madigele; Lebogang Moeti (African Journal of Pentecostal Studies, 2024)
Background: What a couple does in preparation for marriage is a critical determinant of the success of the marriage. It is believed that, that period helps sustain marriages because it gives couples knowledge and skills that can help them in the marriage as well as facilitate their decision-making process. Despite availability of premarital counselling (PMC) services worldwide, many marriages still end in divorce.